Analysis Of Home Foot Temperature Monitoring Intervention in Diabetic Foot Ulcer Patients: Literature Review - Dewinta Adelia; Sri Murthi Lestari; Lisbet Tiurmaida; Cau Kim Jiu (Universitas Muhammadiyah Manado, 2024)
Introduction: High blood sugar can cause neuropathy and peripheral artery disease, reducing sensation in the limbs and leading to diabetic foot ulcers (DFU), about 30% of diabetics develop DFU. The purpose of this study was to analyze the intervention of home foot temperature monitoring in patients with diabetic foot ulcers (DFU). Methods: using the PICO formulation to conduct a literature search collection of materials from databases such as PubMed, Google Scholar, and science direct. The search was conducted using relevant keywords,and focused on articles published between 2021 and 2024 according to the inclusion and exclusion criteria. Results: Low compliance in reducing activities after detecting hotspots hinders ulcer prevention, especially in those with high self-care scores. Home foot temperature monitoring is ineffective without activity reduction, requiring behavioral changes and a comprehensive approach. Sensor-based smart footwear better prevents ulcers by reducing plantar pressure, while telehealth and interactive dashboards enhance patient monitoring and communication for more efficient care. Conclusion: The articles stress combining behavior change and technology to prevent diabetic foot ulcers. Low activity reduction limits effectiveness, but smart footwear aids prevention, while telehealth improves monitoring and communication, highlighting integrated solutions.